مساهمة الإعلام السياحي المرئي في تفعيل التنمية السياحية في الجزائر: قراءة وصفية لبرامج قناة شمس السياحية - شعبان، كريمة Shaaban, Karimah (جامعة الجزائر1 بن يوسف بن خدة, 2021)
This study aims to approach the reality of tourism media in Algeria and highlight its role in the development of the tourism sector, where the latter has become an industry in its own right and is considered one of the important sectors supporting the national economy through the revenues it can generate, and tourism media is considered the physical guide to the tourism industry through its contribution effectively to tourism development in Algeria, where its importance stems in the role it can play in tourism attractions, and improve the image of Algeria tourist abroad by conveying a positive image On local tourism, this study is based on the reality of investing in the tourism media in the promotion of the tourism sector in Algeria, by extrapolating the contents of the Shams tourist channel and reading it descriptively to see the level of keeping up with the tourism development in Algeria, and a number of results have been reached, the most important of which is the need to strengthen the tourism sector with other channels as well as to invest in the digital environment through the establishment of sites and platforms that contribute to the promotion of the Algerian tourism product.
تهدف هذه الدراسة إلى الاقتراب من واقع الإعلام السياحي في الجزائر وإبراز دوره في تطوير قطاع السياحة حيث أصبح هذا الأخير صناعة قائمة بحد ذاتها وهو يعتبر من القطاعات الهامة الداعمة للاقتصاد الوطني من خلال العائدات التي يمكن أن يدرها عليه، ويعتبر الإعلام السياحي الدليل المادي للصناعة السياحية من خلال مساهمته بفعالية في التنمية السياحية في الجزائر حيث تنبع أهميته في الدور الذي يمكن أن يؤديه في الجذب السياحي، وتحسين صورة الجزائر سياحيا في الخارج من خلال نقل صورة إيجابية عن السياحة المحلية، وعليه تقف هذه الدراسة على واقع استثمار الإعلام السياحي المرئي في ترقية القطاع السياحي في الجزائر، باستقراء مضامين قناة شمس السياحية وقراءتها قراءة وصفية لمعرفة مستوى مواكبتها للتنمية السياحية في الجزائر، وقد تم التوصل إلى جملة من النتائج أهمها :ضرورة تدعيم القطاع السياحي بقنوات أخرى فضلا عن الاستثمار في البيئة الرقمية من خلال إنشاء مواقع ومنصات تساهم في الترويج للمنتوج السياحي الجزائري.
Keywords: الترويج السياحي -- الإعلام السياحي -- التنمية السياحية -- الجزائر